Financial strain, health behaviors, and psychological well-being of family caregivers of older adults during the COVID-19 pandemic - Yujun Liu; M. Courtney Hughes; Heng Wang (Elsevier, 2024)
Objectives: This study aims to examine the change in financial strain, health behaviors, and psychological well-being of family caregivers of older adults during the COVID-19 pandemic and explore the differences in mental health outcomes by gender, race, and relationship status. Methods: Using the 2020 National Health and Aging Trends Study COVID-19 supplement, our sample included 2026 family caregivers of older adults. Structural equation modeling was conducted. Results: Caregivers with financial strain showed worse mental health than those with no financial strain. Female or adult children caregivers reported significantly less time walking, more financial strain, and a higher level of negative mental health outcomes compared to male or spouse caregivers; non-White caregivers reported greater positive mental health outcomes compared to White caregivers during the pandemic. Discussion: Health professionals should consider the financial and mental health impact of COVID-19 among family caregivers when designing and delivering caregiver support programs. Innovation: This study provides nationally representative estimates of several important health behaviors and health outcomes for caregivers of older adults during and after the COVID-19 pandemic, helping to fill the knowledge gap about the characteristics of caregivers whose health and well-being were most affected by the pandemic.